2013
DOI: 10.1128/jb.00290-13
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Utilizes D-Glucosaminate via a Mannose Family Phosphotransferase System Permease and Associated Enzymes

Abstract: Salmonella enterica is a globally significant bacterial food-borne pathogen that utilizes a variety of carbon sources. We report here that Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) uses D-glucosaminate (2-amino-2-deoxy-D-gluconic acid) as a carbon and nitrogen source via a previously uncharacterized mannose family phosphotransferase system (PTS) permease, and we designate the genes encoding the permease dgaABCD (D-glucosaminate PTS permease components EIIA, EIIB, EIIC, and EIID).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 71 publications
0
35
0
Order By: Relevance
“…For example, the PTS Man transports mannose, glucose, and in some bacteria also several other carbohydrates albeit with low efficiency. This PTS family shows the greatest variability in transported substrates; its members also catalyze the uptake of less-common carbon sources such as gluconate (7), D-glucosaminate (8), sorbose (9), D-ribitol (10), lacto-N-biose, and galacto-N-biose (11).…”
mentioning
confidence: 99%
“…For example, the PTS Man transports mannose, glucose, and in some bacteria also several other carbohydrates albeit with low efficiency. This PTS family shows the greatest variability in transported substrates; its members also catalyze the uptake of less-common carbon sources such as gluconate (7), D-glucosaminate (8), sorbose (9), D-ribitol (10), lacto-N-biose, and galacto-N-biose (11).…”
mentioning
confidence: 99%
“…The latter is a monomer which results from the breakdown of pectic polymers (34). Furthermore, Goudeau et al reported that genes involved in the uptake of gluconate and idonate (metabolized via the Entner-Doudoroff pathway) were upregulated in Salmonella grown on lettuce leaf macerate caused by D. dadantii (12,(33)(34)(35).…”
Section: Figmentioning
confidence: 99%
“…Eda is involved in the conversion of the phosphorylated KDG molecule (KDPG) into pyruvate and glyceraldehyde-3-phosphate, which feeds into the tricarboxylic acid (TCA) cycle. It has been reported that eda is important for growth of Salmonella on D-gluconate and D-glucuronate (33). The latter is a monomer which results from the breakdown of pectic polymers (34).…”
Section: Figmentioning
confidence: 99%
“…One of these activators, DgaR, regulates expression of the dgaABCDEF operon, which encodes a PTS and enzymes for the transport and catabolism D-glucosaminate (36). DgaR has the conserved histidine required for activation (His-497), and glucose inhibits D-glucosaminate utilization in S. Typhimurium (36).…”
mentioning
confidence: 99%
“…One of these activators, DgaR, regulates expression of the dgaABCDEF operon, which encodes a PTS and enzymes for the transport and catabolism D-glucosaminate (36). DgaR has the conserved histidine required for activation (His-497), and glucose inhibits D-glucosaminate utilization in S. Typhimurium (36). The other LevR-like activator (SL1344_0559) presumably stimulates transcription of a PTS operon of unknown function, and like GfrR, this activator has a tyrosine residue (Tyr-476) in place of the activating histidine; therefore, its activity likely is insensitive to carbon catabolite repression.…”
mentioning
confidence: 99%